Problems of cross-cultural communication; Journal of Economics and Social Sciences; № 7 - Roganova A. D.; Demyanets A. V.; Leontyeva E. G. Elena Gennadievna; Stupnikova O. B. Olga Borisovna (Социологические науки, 2015)
Title screen